Uso de la Ractopamina adicionado en la dieta en la etapa de finalización en pavos de engorde - Vecilla Contreras, Luis Antonio (2022)
The increase in the consumption of turkey meat has had higher production rates in recent years, especially for Christmas dates, due to these, poultry farmers have developed new strategies in food improvement, such as adding ractopamine hydrochloride as growth promoter, in order to obtain quality meat in the established time and with less presence of fatty infiltration. This product is used in the finishing stage in fattening turkeys since it is where the drug will have a greater efficiency in its operation, which has the function of improving feed conversion and in turn promoting an increase in daily weight gain. The information obtained was carried out through the technique of analysis, synthesis and summary with topics related to the use of ractopamine added in the finishing stage, in fattening turkeys. Due to the above, it was determined that the use of ractopamine supplementation in fattening turkeys will allow improvements in weight gain and meet the needs of consumers.